Age stratified sex‐related differences in incidence, management, and outcomes of cardiogenic shock. Issue 7 (7th April 2022) - Osman, Mohammed; Syed, Moinuddin; Kheiri, Babikir; Bianco, Christopher; Kalra, Ankur; Cigarroa, Joaquin E.; Mamas, Mamas A.; Dawn Abbott, Jinnette; Grines, Cindy L.; Fonarow, Gregg C.; Balla, Sudarshan
Abstract: Background: There is a lack of data on age‐stratified sex differences in the incidence, treatment, and outcomes of cardiogenic shock (CS). We sought to study these differences from a contemporary database. Methods: Patients admitted with CS (2004–2018) were identified from the United States National Inpatient Sample. We compared CS (acute myocardial infarction‐related cardiogenic shock [AMI‐CS] and non‐acute myocardial infarction‐related cardiogenic shock [Non‐AMI‐CS]) incidence, management, and outcomes in males and females, stratified into four age groups (20–44, 45–64, 65–84, and ≥85 years of age). Propensity score matching (PSM) was used for adjustment. Results: A total of 1, 506, 281 weighted hospitalizations for CS were included (AMI‐CS, 39%; Non‐AMI‐CS, 61%). Across all age groups, females had a lower incidence of CS compared with males. After PSM and among the AMI‐CS cohort, higher mortality among females compared with males was observed in the age groups 45–64 (28.5% vs. 26.3%) and 65–84 years (39.3% vs. 37.9%) ( p  < 0.01, for all). Among the Non‐AMI‐CS cohort, higher mortality among females compared with males was observed in the age groups 20–44 (33.5% vs. 30.5%), 45–64 (35.1% vs. 31.9%), and 65–84 years (41.7% vs. 40.3%) ( p  < 0.01, for all). Similar age‐dependent differences in the management of CS were also observed between females and males. Conclusions: Females have a lower incidence of CS regardless of age. Significant disparities in the management and outcomes of CS were observed based on sex. However, these disparities varied by age and etiology of CS (AMI‐CS vs. Non‐AMI‐CS) with pronounced disparity among females in the age range of 45–84 years.